Indonesians, Not Using Indonesian: Indonesian Students’ at the University of Nottingham’s Preference to Use English and/or Chinese on WeChat Moments - Nathania, Nadia (Beyond Words, 2017)
WeChat is one of the world’s leading mobile application that has over one billion users inside and outside of China. WeChat is actively used by a group of approximately one hundred Indonesian students studying in the University of Nottingham Ningbo, China due to its convenience as a communication platform while studying in China. This study focuses on how language users accommodate each other, while showing identities and language attitudes through their choice of language in their digital practices on WeChat. The investigation has shown how Indonesian students in UNNC likely prefer to post on WeChat Moments using English and/or Chinese instead of Indonesia. It has pointed out how the participants have created a pattern of language preferences used on WeChat Moments to accommodate their contacts by converging with them and also diverging from them creating a unique identity as Indonesian students in UNNC. Their language preferences result from their attitudes of the English, Chinese and Indonesian language individually affected by social and political factors in their community